A Scorecard for Energy Reform in Developing Countries - Bacon, Robert (World Bank, Washington, DC, 2012)
Only a handful of developing countries have fully reformed their energy sector - oil, gas, and power. A World Bank Survey of 115 developing countries shows that on average, in mid-1998 just 39 percent of key reform steps had been carried out. There are large variations among countries in the number of reform steps take, with most reforms concentrated in a small number of countries. In a great majority of countries, little or no reform has been done. This paper compares the results of the survey across regions and countries, and looks at how private investment has influenced the reforms.